Kedudukan Kurikulum dalam Mewujudkan Pendidikan Multikulturalisme - Amalia, Mukhlisatinnisa; Sofi’i, Muhammad; Fitri, Nurul Lahdilah; Mukholik, Idghom; Sabhara, Harun (ARZUSIN, 2022)
This study aims to analyze and think about the position of multiculturalism in the education curriculum in Indonesia. The position of multicultural education in Indonesia is as an alternative means of conflict resolution, multicultural as an alternative so that students do not leave cultural roots, and towards a multicultural Indonesian society. This research uses a qualitative approach which is carried out descriptively. With the aim of being able to study more deeply related to the position of multicultural education in the education curriculum in Indonesia. Developing an educational curriculum for a country as large and diverse as Indonesia,such as social diversity,culture,political ambition, and certain economic capabilities are important considerations for decision makers in educational programs. The diversity of people,cultures,political ambitions and economic capabilities is a reality that cannot be ignored. This diversity should form the structure of curriculum preparation. However this diversity is rarely taken seriously and is therefore often overlooked by those in curriculum development authority. This study aims to analyze and think about the position of multiculturalism in the education curriculum in Indonesia. The position of multicultural education in Indonesia is as an alternative means of conflict resolution, multicultural as an alternative so that students do not leave cultural roots, and towards a multicultural Indonesian society. This research uses a qualitative approach which is carried out descriptively. With the aim of being able to study more deeply related to the position of multicultural education in the education curriculum in Indonesia. Developing an educational curriculum for a country as large and diverse as Indonesia,such as social diversity,culture,political ambition, and certain economic capabilities are important considerations for decision makers in educational programs. The diversity of people,cultures,political ambitions and economic capabilities is a reality that cannot be ignored. This diversity should form the structure of curriculum preparation. However this diversity is rarely taken seriously and is therefore often overlooked by those in curriculum development authority.